THEORETICAL BASIS OF THE USE OF HEURISTIC TASKS IN THE LEARNING PROCESS - Zarifboy, Sobirov (PT. Antis International Publisher, 2025)
Objective: This study aims to examine the theoretical foundations of heuristic education and assess the effectiveness of heuristic tasks in fostering students' intellectual independence, research skills, and creative thinking within general secondary education. Method: A qualitative research approach was employed, involving theoretical analysis of classical and modern pedagogical works, as well as a review of educational reforms and practices in Uzbekistan. Results: The findings indicate that heuristic methods—such as tasks, guided conversations, and problem-based questioning—play a significant role in developing students' logical reasoning, creativity, and research capabilities. However, despite their cognitive and developmental potential, these strategies remain underutilized in mainstream curricula. Novelty: This study provides a comprehensive synthesis of heuristic education by integrating insights from both Eastern and Western philosophical traditions with contemporary pedagogical models. It highlights the relevance of heuristic strategies in 21st-century education and emphasizes their transformative role in shifting learning from passive reception to active inquiry.